Application of the theory statically indeterminate structures of infinite degree to a cable-truss footbridge under lateral forces. (1st June 2019) - Illouli, S.; Sadaoui, A.; Khennane, A.
Highlights: Development of closed form solutions for lateral forces on a cable truss. Theory of statically indeterminate structures of infinite degree. Fredholm integral equations. Reaction density. Abstract: A simplified method based on the theory of statically indeterminate structures of infinite degree is proposed to analyse the response of cable truss bridges under lateral loads. The bridge consists of two major cables anchored at their ends and a series of pin-ended hangers attached to the cables supporting a lightweight deck whose stiffness can be neglected. Assuming the hangers can be replaced by a continuous inextensible diaphragm, it will be shown that under the action of lateral loads, the diaphragm exerts on the cables a restitution force that can be assimilated to a reaction density. Writing the equations of static equilibrium of the cables under these conditions leads to a Fredholm integral equation whose solution is actually the unknown reaction density. The solution of the equation obtained through numerical integration was found to be in good agreement with the finite element method across different configurations of lateral loads. The method was subsequently used to carry a parametric study on the effects of some important parameters such as the initial pre-stress adjustment in the deck cable, and self-weight on the stability of the bridge to lateral loads. The method is robust yet simple to use; a detailed example of its implementation is given as the Appendix.